Mobility of professors in the university system of the Russian Empire of the 19th and the beginning of the 20th centuries - Andrei Andreev (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2020)
The article is devoted to the study of a general and topical problem in the history of Russian universities, namely professors’ mobility, i.e. relocation of professors between universities of the Russian Empire in the course of their academic careers. This process has been studied throughout the entire existence of the system of Russian universities up to 1914. The spatial scope of the work includes all universities of the Russian Empire subordinated to the Ministry of Public Education and subject to similar legislation, which provides a unifi ed view of them as a university system. For the most complete and detailed study of mobility, on the basis of a complete prosopographic database of Russian professors, an auxiliary database was compiled, which collected information about those of them who moved from one university to another. Data on 522 such professorial transitions are analyzed using graphs and tables. The general dynamics of the process was revealed, which made it possible to prove that in the late XIX — early XX centuries. mobility was an essential and very common phenomenon for the career of a university professor in Russia. Shown is the role that mobility played when privat-docents received free professorial positions. The reverse process was also discovered, when professors moved to another university for the position of privatdocent, compensating for the loss of status with other capabilities of the scientifi c and educational system. The distribution of transitions between specifi c universities was also constructed, pairs were identifi ed between which these transitions were especially frequent, universities were revealed where the number of professors who left from there was the most high, and, on the contrary, universities, where a signifi cant number of scientists moved to. Chains of transitions were also considered, which could reach up to three or four subsequent transfers between universities. Based on this analysis, a conclusion was made about the presence of several types — «starting», «transferring» and «terminal» universities in the Russian Empire. The average duration of a professor’s position before transferring to another university was calculated; Based on its general distribution, various groups of reasons are shown that stimulated both young and age scientists to change their place.